HUBUNGAN MATHEMATICS SELF-EFFICACY DAN MATH ANXIETY DI SISWA SMP DI YOGYAKARTA - Yoel Christian Sukasno; Reny Yuniasanti (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Students’ ability to engage in mathematics learning is determined not only by their mastery of concepts but also by the psychological conditions accompanying the learning process. One issue that remains prevalent at the junior high school level is the emergence of math anxiety, which may hinder students’ engagement and academic performance. This study explores the relationship between mathematics self-efficacy and math anxiety among junior high school students in Yogyakarta. The study employed a quantitative correlational approach using pre-test data from 187 eighth-grade students from four public and private junior high schools. Data were collected through a 23-item mathematics self-efficacy questionnaire and a 14-item math anxiety questionnaire using a Likert scale. The quality of the instruments was supported by good reliability values, as indicated by Cronbach’s alpha coefficients of 0.856 for mathematics self-efficacy and 0.874 for math anxiety. The analysis showed that the data met the assumptions of normality and linearity, making them suitable for Pearson correlation analysis. [M2.1]A significant negative relationship was found between the two variables, indicating that an increase in students’ confidence in their mathematical abilities was associated with a decrease in their level of anxiety in mathematics learning. These findings reinforce the importance of developing students’ psychological aspects as an integral part of mathematics learning strategies that support well-being and academic success. ABSTRAK Kemampuan siswa dalam menghadapi pembelajaran matematika tidak hanya ditentukan oleh penguasaan konsep, tetapi juga oleh kondisi psikologis yang menyertai proses belajar. Salah satu isu yang masih banyak ditemukan pada jenjang Sekolah Menengah Pertama adalah munculnya math anxiety yang dapat menghambat keterlibatan dan performa akademik siswa. Penelitian ini mengeksplorasi keterkaitan antara mathematics self-efficacy dan math anxiety pada siswa SMP di Yogyakarta. Kajian dilakukan menggunakan pendekatan kuantitatif korelasional dengan memanfaatkan data pre-test dari 187 siswa kelas VIII yang berasal dari empat SMP negeri dan swasta. Pengumpulan data dilakukan melalui angket mathematics self-efficacy sebanyak 23 butir dan angket math anxiety sebanyak 14 butir dengan skala Likert. Kualitas instrumen didukung oleh nilai reliabilitas yang baik, ditunjukkan melalui koefisien Cronbach’s alpha sebesar 0,856 untuk mathematics self-efficacy dan 0,874 untuk math anxiety. Hasil analisis menunjukkan bahwa data memenuhi asumsi normalitas dan linearitas sehingga layak dianalisis menggunakan korelasi Pearson. Hubungan negatif yang signifikan ditemukan antara kedua variabel yang mengindikasikan bahwa peningkatan keyakinan siswa terhadap kemampuan matematisnya berkaitan dengan penurunan tingkat kecemasan dalam pembelajaran matematika. Temuan ini memperkuat pentingnya pengembangan aspek psikologis siswa sebagai bagian integral dari strategi pembelajaran matematika yang mendukung kesejahteraan dan keberhasilan belajar.